A lightweight privacy-preserving and sharing scheme with dual-blockchain for intelligent pricing system of smart grid. Issue 103 (April 2021) - Li, Kunchang; Yang, Yifan; Wang, Shuhao; Shi, Runhua; Li, Jianbin
Abstract: With the deepening of the application of information technology, the development trend of smart grid as the next generation grid has pointed the way for the development of energy internet in the power industry. To protect the privacy of participants, this paper proposes a lightweight dual-blockchain privacy protection and sharing solution for smart grid intelligent pricing systems. We design a lightweight distributed cloud storage architecture based on dual blockchains. The cloud storage architecture stores the encrypted data and returns the address, thereby protecting the privacy of the data. A private blockchain is used to map the association between real identity and pseudonym. At the same time, a new shared blockchain is created for nodes with access control to reduce cost, ensure security and access resource on-demand. Then, secure signature authentication and identity-based proxy re-encryption strategies are designed. Encryption and bilinear pair-based signature scheme is used to aggregate data to support low-cost and high-performance computing. The evaluation results show that the scheme has the advantages of low latency, low response time and small storage cost, and can meet the growing demand for secure communication of full-service data of the smart grid.